2021
DOI: 10.1371/journal.pone.0248384
|View full text |Cite
|
Sign up to set email alerts
|

Don’t put all social network sites in one basket: Facebook, Instagram, Twitter, TikTok, and their relations with well-being during the COVID-19 pandemic

Abstract: Prior studies indicated that actively using social network sites (SNSs) is positively associated with well-being by enhancing social support and feelings of connectedness. Conversely, passively using SNSs is negatively associated with well-being by fostering upward social comparison and envy. However, the majority of these studies has focused on Facebook. The present research examined the relationships between well-being—satisfaction with life, negative affect, positive affect—and using actively or passively v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
71
3
10

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(90 citation statements)
references
References 36 publications
6
71
3
10
Order By: Relevance
“…Despite the fact that there is research that points to the expression of negative feelings during the pandemic through Twitter [76][77][78], the results of this study are aligned with other works that impact the possibility of using Twitter constructively during the COVID-19 crisis and report a use of the network incorporating positive and socially supportive values [79][80][81].…”
Section: Discussionsupporting
confidence: 79%
“…Despite the fact that there is research that points to the expression of negative feelings during the pandemic through Twitter [76][77][78], the results of this study are aligned with other works that impact the possibility of using Twitter constructively during the COVID-19 crisis and report a use of the network incorporating positive and socially supportive values [79][80][81].…”
Section: Discussionsupporting
confidence: 79%
“…However, researchers who have studied the role of social media (mainly Facebook) on users’ well-being, self-esteem, depression symptoms, and anxiety have presented mixed findings regarding the significant association with a potential explanation based on passive or active use (Escobar-Viera et al, 2020 ). A recent study regarding social support and feelings of connectedness over the COVID-19 pandemic has shown the passive usage of Facebook is negatively related to well-being through upward social comparison, whereas active usage of Instagram is positively related to satisfaction with life and negative affect through social support (Masciantonio et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In a survey that involved French, Belgian and Swiss participants, the prevalence also varied by social media platform [33] . The prevalence was 15% for Tik Tok (video), 38% for Twitter (text), 63% for Instagram (photos) and 89% for Facebook (text and photos) [33] .One of the U.S. studies in this review only surveyed Facebook use (much like the pre-COVID studies) and reported 70% pre-COVID but a 27% increase during COVID to 97% Facebook use [34] , which was the same prevalence (98%) reported in another U.S. COVID survey [35] .…”
Section: Prevalence Of Social Media Use By Youth During Covid-19mentioning
confidence: 99%
“…In a study that tapped social media use in French, Belgian and Swiss youth during lockdown (N= 793), overall use significantly increased [33] . Surprisingly, active use of social network sites (messaging and responding to messages) increased the well-being of students via improving social capital and connectedness [33] . In contrast, passive use (viewing messages on the site) decreased the well-being of students by fostering social comparison and envy.…”
Section: Active Versus Passive Use Of Social Networking Sitesmentioning
confidence: 99%